Cultural and humanitarian relations Kazakhstan and Japan - Zadakyzy Zһ. (Journal of Oriental Studies, 2016)
Kazakhstan and Japan in the system of political and economic relations are closer mutually benefi cial cooperation. At the present stage of the Sino-Kazakh relations is important to note the role of not only economic interests, but also cultural and humanitarian. This article analyzes the critical components of scientifi c relations. Also the author of widely used terms like "humanitarian-cultural aspects" of relations of Japan and Kazakhstan. In particular, it is dominated by an emphasis on the fact that the development in the humanitarian and cultural must come from the real needs of today’s society.